2015
DOI: 10.1038/cdd.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

Fyn-phosphorylated PIKE-A binds and inhibits AMPK signaling, blocking its tumor suppressive activity

Abstract: The AMP-activated protein kinase, a key regulator of energy homeostasis, has a critical role in metabolic disorders and cancers. AMPK is mainly regulated by cellular AMP and phosphorylation by upstream kinases. Here, we show that PIKE-A binds to AMPK and blocks its tumor suppressive actions, which are mediated by tyrosine kinase Fyn. PIKE-A directly interacts with AMPK catalytic alpha subunit and impairs T172 phosphorylation, leading to repression of its kinase activity on the downstream targets. Mutation of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Consequently, ablation of PIKE in the muscle protects the animals from developing excess weight gain, ectopic lipid accumulation, and diabetes development. Combining our recent discoveries that PIKE-A prevents AMPK phosphorylation by liver kinase B1 or Ca 2+ /calmodulin-dependent protein kinase kinase β (42) and the findings reported in this study, we propose a model that obesity development causes an elevation of circulating TNF-α, which triggers the formation of PIKE-A/AMPK complex in the skeletal muscle. Binding of PIKE-A to AMPK shields the T172 site from being phosphorylated by the upstream kinases.…”
Section: Discussionsupporting
confidence: 71%
“…Consequently, ablation of PIKE in the muscle protects the animals from developing excess weight gain, ectopic lipid accumulation, and diabetes development. Combining our recent discoveries that PIKE-A prevents AMPK phosphorylation by liver kinase B1 or Ca 2+ /calmodulin-dependent protein kinase kinase β (42) and the findings reported in this study, we propose a model that obesity development causes an elevation of circulating TNF-α, which triggers the formation of PIKE-A/AMPK complex in the skeletal muscle. Binding of PIKE-A to AMPK shields the T172 site from being phosphorylated by the upstream kinases.…”
Section: Discussionsupporting
confidence: 71%
“…As Saracatinib and Dasatinib are non-specific inhibitors of individual SFK member 26 , the genetic inhibition of FYN remains the best option to study its functions in glioma biology. Indeed, genetic downregulation of FYN expression inhibited glioma cells migration and proliferation in vitro 3,8,9,27 , yet failed to affect glioma progression in vivo immune suppressive mice 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrated that Fyn is a novel potential target in antitumor drug treatment [20]; for example, Fyn is a key molecule in mediating breast cancer epithelial-mesenchymal transition regulation through FOXO1, which is mediated by FGF2 induced the activation of PI3K/AKT and ERK/MAPK pathways [21]. Fyn was reported to mediate the phosphorylation of PIKE-A at site T172 that inhibits AMPK signaling pathway, and results in blocking glioblastoma cell suppression activity [22].…”
Section: Discussionmentioning
confidence: 99%